Impact of Prevention on Future Cancer Incidence in Australia - Youl, Philippa; Baade, Peter; Meng, Xingqiong (Australian Cancer Society, 2012)
Cancer, along with other chronic diseases such as cardiovascular disease, is recognised as one of the most common public health threats in Australia. This burden and associated financial cost to the community will continue to increase given Australia’s increasing and aging population. Projections based on population growth and aging have estimated that there will be about 170,000 new cancers diagnosed in 2025. However, there is some potential for optimism given that only about 5-10% of cancers are caused by genetic or inherited disorders. The World Health Organisation suggests that at least one third of all cancer cases are preventable with a reduction in the prevalence of risk factors such as tobacco smoking, poor nutrition and diet, physical inactivity, alcohol consumption, occupational exposure and sun exposure, offers the most cost-effective long-term strategy for the control of cancer. While we have witnessed significant declines in the prevalence of tobacco smoking, there is little evidence that there have been any significant reductions in the prevalence of other known behavioural risk factors. Clearly, large-scale and long-term preventive strategies are required and if fully implemented, can have the potential to prevent nearly 57,000 new cancers in 2025 alone.